Synthesis, Characterization and Effect of bis-1,3,4Oxadiazole Containing Glycine Moiety on the Activity of Some Transferase Enzymes. - Tomi, I. H. R.; Al-Qaisi, A. H. J.; Al-Qaisi, Z. H. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
We described herein the synthesis of novel bis-1,3,4-oxadiazole containing glycine moiety. N-5-[5-(4-methoxyphenyl)-1,3,4-oxadiazole-2-yl-sulfanyl]-1,3,4-oxadiazole-2-yl-methyl-4methoxybenzamide was fully characterized by elemental analysis, FT-IR and 1H NMR spectroscopy. Also this study was designed to show the effects of bis-oxadiazole compound on the activities of some transferase enzymes such as: GOT, GPT and Î³-GT in sera. This compound demonstrated activation on GOT and GPT activities, inhibitory effects on the Î³-GT activity. These effects increased with the increasing of the concentration of the compound. The causes of the increases and decreases in the enzymes activities are discussed